Characteristics of occurrence and distribution rule of deep coalbed methane in supercritical state - Lihong ZHOU; Xia YAN; Xianyue XIONG; Feng WANG; Wenchao LIU; Yuejie YANG; Zhaobiao YANG; Yanqing FENG (Meitan kexue jishu)
Deep Coalbed methane(CBM) has become an important direction for gas storage and production, but its original occurrence state of adsorbed gas and free gas and distribution law under different geological conditions are unclear, which restricts the accurate estimation of deep CBM reserves and the understanding of production law. With the increase of burial depth, temperature and pressure, methane enters the supercritical phase, its fluid density will continue to increase, and its viscosity is similar to that of the gas phase, indicating that the current understanding has underestimated the amount of free gas resources and the flow ability of fluid easy to produce. Under high temperature and high pressure in deep coal seams, the “supercritical fluid characteristics” of methane are more significant and cannot be ignored. The current gas content calculation method based on reservoir pressure does not take into account the fact that the fluid pressure inside the coal seam micropores is higher than the reservoir pressure, that is, the existence of a “overpressure in micropores” environment, so the actual gas content is underestimated. A calculation model for the content of free gas and adsorbed gas in deep coalbed methane considering the characteristics of overpressure in micropores and methane supercritical fluid was established based on the variation of methane physical properties with pressure and temperature, as well as the theory of overpressure in micropores, targeting the deepest coal seam burial depth in China up to 5000 m and coal rank range of 0.8% to 3.0%. The results show that: ① Under high temperature and high pressure, methane viscosity, density, compression factor, volume coefficient and other high pressure physical property parameters do not change linearly with temperature and pressure. Based on the quantitative relationship between high pressure physical property parameters and temperature and pressure, empirical calculation formulas for each parameter are established. ② The distribution law of adsorbed gas and free gas occurrence states in deep CBM is revealed under different thermal evolution degrees, different burial depths and different temperature and pressure conditions. At the same depth, with the increase of coal rank, the adsorbed gas content is increasing, the free gas content is decreasing, and the proportion of free gas is decreasing. With the increase of coal seam depth, the content of adsorbed gas increases first and then decreases, but the proportion of free gas increases gradually. ③ Considering the influence of methane supercritical fluid properties on adsorption, compared to the same situation where this feature is ignored, the actual adsorbed gas content is not as high as the existing understanding, and the proportion of adsorbed gas is reduced by 6%−9%.④ Four model methods were established to clarify the critical transition depth of gas content, and the variation laws and charts of adsorbed gas/free gas at different coal ranks, porosity and water saturation. ⑤ Based on the new understanding of “overpressure in micro pores and normal reservoir pressure in macro pores” a new calculation method for free gas and adsorbed gas content considering “overpressure in micro pores +supercritical state” has been established. Compared with traditional methods that only consider reservoir pressure, the calculation results are more in line with production reality. When the burial depth of Daji Block reaches 2 000 m, the proportion of free gas in high rank coal seams can conservatively reach 41%, an increase of 20% compared to existing understanding. The research results can provide scientific theoretical basis for revealing the distribution law of deep coalbed methane occurrence and reserve evaluation.